Maximizing benefit transfers to the poor: evidence from South African employment programmes - Haddad, Lawrence J.; Adato, Michelle (International Labour Office, 2002)
Targeted public works programmes (PWPs) seek to create physical assets at wages not exceeding market wages for comparable work. But what is their success at poverty reduction, genuine job creation and their performance relative to that of untargeted benefit transfer programmes? Drawing on new data from South Africa, the authors focus on 101 projects in seven PWPs in Western Cape Province, in the mid-1990s. They estimate the rands of public expenditure needed to transfer one rand to the poor, then compare this ratio with that generated by a hypothetical, untargeted transfer programme. Most of the PWPs considerably outperform the benchmark.